The Association of IFI27 Expression and Fatigue Intensification during Localized Radiation Therapy: Implication of a Para-Inflammatory Bystander Response - Hsiao, Chao-Pin (Molecular Diversity Preservation International (MDPI), 2013)
The mechanisms behind fatigue intensification during cancer therapy remain elusive. The interferon alpha-inducible protein 27 (IFI27) was the most up-regulated gene based on our previous microarray data in fatigued men with non-metastatic prostate cancer receiving localized external beam radiation therapy (EBRT). The purpose of this study was to confirm the IFI27 up-regulation and determine its association with fatigue intensification during EBRT. Peripheral blood samples and fatigue scores were collected at three time points—prior to EBRT, at midpoint, and at completion of EBRT. Confirmatory quantitative real time polymerase chain reaction (qPCR) and enzyme-linked immunosorbent assay (ELISA) were utilized to verify the microarray results. Subjects were a total of 40 Caucasian men with prostate cancer; 20 scheduled for EBRT (65.6 ± 7.5 years old), and 20 on active surveillance as controls (62.8 ± 6.1 years old). Significant IFI27 expression overtime during EBRT was confirmed by qPCR (p < 0.5), which correlated with fatigue scores during EBRT (R = −0.90, p = 0.006). Alterations in mechanisms associated with immune response and mitochondrial function that explain the up-regulation of IFI27 may provide an understanding of the pathways related to the intensification of fatigue during localized radiation therapy.